Pelvic pressure packing for intractable obstetric and gynaecological hemorrhage in a tertiary care hospital - Bhosale, Archana; S., Kavya H.; Nandanwar, Yogeshwar Sadashiv; Ansari, Ayesha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Haemorrhage is one of the most common complication of any surgery. Haemorrhage can be arterial, venous or capillary ooze. Massive haemorrhage if not timely managed may lead to fatal consequences. There are various medical and surgical methods to control haemorrhage. This study aims to achieve hemostasis with the help of pelvic pressure pack in Obstetric and Gynaecologic surgeries when standard methods are failed and to evaluate efficacy of simple and modified technique of pack preparation. Methods: This is an observational study of 11 cases conducted over a period of 4yrs. This study reports modification of standard packing techniques which overcomes some of its limitations. Here the pack was used in different gynaecologic and Obstetric cases, where intractable haemorrhage was the major problem and standard methods to control haemorrhage had failed. Here a simple foley’s catheter rolled with condom and filled with normal saline was used to prepare a pack and kept over the bleeding surface. This specific pack will adopt the shape of the body cavity it is inserted into, thereby causing pressure tamponade against bleeding surfaces. Pack was removed after 48-72 hours of insertion. Postoperative control of bleeding, patient stability and morbidity were studied. Results: The pelvic pressure pack successfully controlled bleeding in 100% of cases without any morbidity and mortality. Conclusions: In the contemporary management of post-hysterectomy or adhesiolysis induced uncontrolled pelvic bleeding and venous oozes, the pelvic pressure pack appears to be valuable and effective option, affording correction of coagulopathy and further stabilization. We believe all Obstetricians and Gynaecologists should be familiar with this simple safe and cheap potentially lifesaving technique.